Economic Gains and Losses for Sustainable Policy Development of Crude Oil Resources: A Historical Perspective of Indian Subcontinent - Raza, Ali; Khokhar, Maryam; Gordillo, Reyna Esperanza Zea; Ejaz, Faisal; Jagirani, Tahir Saeed; Júlia, Fodor Zita; Hossain, Md Billal (International Journal of Energy Economics and Policy, 2024)
Energy fluctuations and global economic directly hit the Indian Subcontinent (Geopolitically, it generally includes the countries of Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka) economy and social welfare, which are the net importer of energy sources. This study investigates the relationship between strategic petroleum reserves and welfare losses for the Indian Subcontinent. The breakdown of the crude oil energy supply significantly impacts energy security & and welfare losses. Oil supply security was quantified in terms of the Indian Subcontinent’s oil vulnerability index (which accounts for 84 percent of global oil imports), and welfare losses based on oil supply disruption were calculated. Afghanistan is the most susceptible country in the Indian Subcontinent regarding energy reserves, as per the composite index results, whereas India is the least vulnerable. Empirical findings pointed to a 30% oil supply deficit as the cause of the most volatile pattern of oil pricing, which exacerbates the estimated welfare loss by a 40% drop in GDP, which is around 700 in the Indian Subcontinent 9000 in the top oil-consuming countries. According to this analysis, the Indian Subcontinent should keep at least a hundred days’ worth of strategic oil resources to avert social and economic losses due to oil price fluctuations.